Pengendapan Logam Tembaga (Cu) dengan Sistem Kimiawi pada Limbah Luaran Kerja Bengkel Elektronika - Aris Fakhrudin; Alrosyid Alrosyid; Mardi Wasono; Basuki Rachmat; Dewi Pujiastuti (Jurnal Pengelolaan Laboratorium Pendidikan, 2026)
Electronics workshop practicums and undergraduate final projects conducted in educational laboratories generate liquid waste containing high concentrations of copper (Cu). This wastewater is acidic, corrosive, and classified as hazardous and toxic waste (B3), posing potential risks to laboratory personnel, equipment, and the environment if not properly managed. A simple and widely applied method for reducing heavy metal concentrations in wastewater is chemical precipitation using alkaline reagents; however, the effectiveness of the precipitating agent strongly depends on wastewater characteristics and operational conditions.This study aimed to optimize the precipitation of copper (Cu) from wastewater generated by printed circuit board (PCB) etching processes in an electronics workshop and to compare the performance of sodium hydroxide (NaOH) and calcium hydroxide [Ca(OH)2] as precipitating agents. Batch experiments were conducted at room temperature with variations in contact time, mixing conditions, and precipitant dosage. Dissolved copper concentrations were determined using Atomic Absorption Spectrophotometry (AAS).The results demonstrate that NaOH provides significantly higher copper removal efficiency than Ca(OH)2. From an initial copper concentration of approximately 2,381 mg/L, precipitation using NaOH without mechanical mixing reduced the Cu concentration to about 19.765 mg/L at an optimum contact time of 10 hours. In the dosage optimization experiments with mixing, the addition of 5 g NaOH achieved the lowest residual copper concentration, approximately 1.67 mg/L. In contrast, Ca(OH)2 under comparable contact time conditions resulted in substantially higher residual copper concentrations, indicating lower effectiveness for the tested wastewater matrix.Based on these findings, it can be concluded that the research objective was achieved, namely identifying the optimum conditions for copper precipitation from electronics workshop wastewater. Sodium hydroxide (NaOH) was proven to be more effective than calcium hydroxide [Ca(OH)2] and has strong potential as a simple, low-cost method for managing hazardous liquid waste in educational laboratories to enhance laboratory safety and environmental compliance.